Hemoglobinopathy SD presenting as Hemoglobinopathy SS - Lissa, Sonia Maria; Bach, Sergio Luiz; Spezia, Juliana; Henneberg, Railson; Silva, Paulo Henrique da (Medicina (Ribeirao Preto), 2017)
This case report shows the interaction of hemoglobin (Hb) S with Hb D. in a child previously diagnosed with sickle cell anemia based on the Hb electrophoretic migration pattern in alkaline pH. The sickling phenomenon was confirmed with 2% sodium metabisulfite. The father and mother of the child had a heterozygous pattern (Hb AS) in hemoglobin electrophoresis at alkaline pH. The sickling phenomenon has been confirmed to the father, but it has not been confirmed for the mother. The electrophoresis at acid pH was used to differentiate Hb S from Hb D. The family’s phenotype was established: the father has Hb AS, the mother AD and, the child SD. The purpose of this study was to emphasize the importance of confirmation of Hb S detected in electrophoresis at alkaline pH, with the solubility test or 2% sodium metabisulfite and with the electrophoresis at acid pH.